A correlação entre jornada de trabalho e produtividade: uma perspectiva macroeconômica entre países - Gaspar, Willians Cesar Rocha (2017)
This research has as general objective to identify the variables or contributing factors to subsidize the discussion about reduction of the Working Day. As a specific objective, what is proposed is to verify how these same variables affect Productivity. For both objectives the macroeconomic aspects of the countries analyzed are considered. The criterion for selecting these countries is based on the "ranking" of the OECD and World Bank database for the year 2013, considering all the major world economies, which together represent 65.22% of global GDP. The data extracted refer to the "Gross Domestic Product - GDP at (PPP) - Purchasing Power Parity", which consists of the Gross Domestic Product, in international dollars, with a view to the comparative possibility of these economies by purchasing power parity (PPP). Other sources of information were considered as objects of analysis and observations, including the statistical series of secondary data from the International Labor Office (ILO), the International Monetary Fund (IMF), the United Nations (UNDP), the Brazilian Institute of Geography and Economics (IBGE), the Department of Statistics and Socioeconomic Studies (DIEESE) and the Institute of Economic and Applied Research (IPEA). The research was conducted at the macroeconomic level of the countries, with a longitudinal temporal cut between the years 2007 and 2013, in order to observe the behavior of these economies, including during the period of the 2008 global crisis. evolution of the historical series of GDP, revealing the size of the economy, GDP per capita, which captures wealth in relation to the population. Finally, we consider the labor productivity factor itself, which deals with the relationship between GDP, the number of people and the number of hours worked in the period. This research has as general objective to identify the variables or contributing factors to subsidize the discussion about reduction of the Working Day. As a specific objective, what is proposed is to verify how these same variables affect Productivity. For both objectives the macroeconomic aspects of the countries analyzed are considered. The criterion for selecting these countries is based on the "ranking" of the OECD and World Bank database for the year 2013, considering all the major world economies, which together represent 65.22% of global GDP. The data extracted refer to the "Gross Domestic Product - GDP at (PPP) - Purchasing Power Parity", which consists of the Gross Domestic Product, in international dollars, with a view to the comparative possibility of these economies by purchasing power parity (PPP). Other sources of information were considered as objects of analysis and observations, including the statistical series of secondary data from the International Labor Office (ILO), the International Monetary Fund (IMF), the United Nations (UNDP), the Brazilian Institute of Geography and Economics (IBGE), the Department of Statistics and Socioeconomic Studies (DIEESE) and the Institute of Economic and Applied Research (IPEA). The research was conducted at the macroeconomic level of the countries, with a longitudinal temporal cut between the years 2007 and 2013, in order to observe the behavior of these economies, including during the period of the 2008 global crisis. evolution of the historical series of GDP, revealing the size of the economy, GDP per capita, which captures wealth relative to the population. Finally, we consider the labor productivity factor itself, which deals with the relationship between GDP, the number of people and the number of hours worked in the period. Design/Methodology/ approach – The method is a qualitative research of the exploratory type, subsidized by quantitative correlation analysis, and the statistical design is directed to the verification of the degree of association between the variables: Working day and Labor productivity; that is, calculation and interpretation of the degree of correlation between these two variables. Findings – In the final conclusion of the study, it is inferred based on the theoretical reference and the analysis of the statistical data, if the reduction in the working day contributes to changes in productivity indexes, and just as other variables are considered in this discussion. Research limitations – No aspects of the national culture, climatic conditions and segregation of nations by percentage of participation in agriculture, industry, and services were considered in the composition of their economies, with a view to performing comparative analysis by subgroups. In addition, the sample set is restricted both in number of countries and in relation to the relatively short period between 2007 and 2013, in addition to being marked by an atypical event such as the global economic crisis of 2008. Practical contributions – To governments, organizations and workers to rethink the possible economic and social benefits, through public policies that allow greater flexibility in working hours, focusing on the competitive advantages and the balance of the relation between labor and capital, observing the legal aspects, productivity, quality of life, unit costs and the generation of jobs